The influence of the basic conditions of the forced feed of abrasive compound on the surfaces roughness of flat ceramic elements after lapping - Barylski , Adam; Gniot, Maciej (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2021)
In standard lapping, the abrasive compound is feed to the machining zone in a continuous manner – either by flooding or by droplets – which generates significant loss of the abrasive. The paper describes an innovative method of dosing and applying the abrasive compound onto the surface of a lapping disc, which eliminates this drawback. Additionally, the results of the examination of the influence of the compound feed on the selected parameters of the surface roughness of ceramic elements after lapping. In the conducted experiments the Authors examined the influence of the percentage content of grinding grains in the carrier, as well as the size of the compound dosage and viscosity of a liquid carrier on the values of particular surface roughness parameters of the lapped sealing elements. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)